Cortical activity associated with the perception of temporal asymmetry in ramped and damped noises - Rupp, André; Spachmann, André; Dettlaff, Anna; Patterson, Roy D. (Basic aspects of hearing, 2013)
Human listeners are very sensitive to the asymmetry of time-reversed pairs of ramped and damped sounds. When the carrier is noise, the hiss component of the perception is stronger in ramped sounds and the drumming component is stronger in damped sounds (Akeroyd and Patterson 1995). In the current study, a paired comparison technique was used to establish the relative “hissiness” of these noises, and the ratings were correlated with (a) components of the auditory evoked field (AEF) produced by these noises and (b) the magnitude of a hissiness feature derived from a model of the internal auditory images produced by these noises (Irino and Patterson 1998). An earlier AEF report indicated that the peak magnitude of the transient N100m response mirrors the perceived salience of the tonal perception (Rupp et al. 2005). The AEFs of 14 subjects were recorded in response to damped/ramped noises with half-lives between 1 and 64 ms and repetition rates between 12.5 and 100 ms. Spatio-temporal source analysis was used to fit the P50m, the P200m, and the sustained field (SF). These noise stimuli did not produce a reliable N100m. The hissiness feature from the auditory model was extracted from a time-averaged sequence of summary auditory images as in Patterson and Irino (1998). The results show that the perceptual measure of hissiness is highly correlated with the hissiness feature from the summary auditory image, and both are highly correlated with the magnitude of the transient P200m. There is a significant but weaker correlation with the SF and a nonsignificant correlation with the P50m. The results suggest that regularity in the carrier effects branching at an early stage of auditory processing with tonal and noisy sounds following separate spatio-temporal routes through the system.